Prognostic significance of nm23-H1 expression in oral squamous cell carcinoma - Wang, Y-F (Nature Publishing Group, 2004)
Recent studies indicated nm23-H1 played a role in cancer progression. Therefore, we investigated clinical significance of nm23-H1 expression in oral squamous cell carcinoma (OSCC). In total, 86 OSCC specimens were immunohistochemically stained with nm23-H1-specific monoclonal antibodies. Immunohistochemical staining of nm23-H1 was confirmed by immunoblotting. The relations between nm23-H1 expression and clinicopathologic variables were evaluated by χ(2) analysis. As increased size of primary tumour could escalate metastatic potential and the data of patients at the late T stage might confound statistical analyses, we thus paid special attention to 54 patients at the early T stage of OSCC. Statistical difference of survival was compared by a log-rank test. Immunohistochemically, nm23-H1 expression was detected in 48.8% (42 out of 86) of tumorous specimens. It positively correlated with larger primary tumour size (P=0.03) and inversely with cigarette-smoking habit (P=0.042). In patients at the early T stage, decreased nm23 expression was associated with increased incidence of lymph node metastasis (P=0.004) and indicated poor survival (P=0.014). Tumour nm23-H1 expression is a prognostic factor for predicting better survival in OSCC patients at the early T stage, which may reflect antimetastatic potential of nm23. Therefore, modulation of nm23-H1 expression in cancer cells can provide a novel possibility of improving therapeutic strategy at this stage. In addition, our results further indicated cigarette smoking could aggravate the extent of nm23-H1 expression and possibly disease progression of OSCC patients.